A Clinical Score to Predict "Corrected Thrombolysis in Myocardial Infarction Frame Count" in Patients With ST-Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention. (April 2022) - Ozkalayci, Flora; Türkyılmaz, Erdem; Karagoz, Ali; Karabay, Can Yucel; Tanboga, İbrahim Halil and Oduncu, Vecih
Corrected thrombolysis in myocardial infarction frame count (cTFC) is an objective, simple, and reproducible method to assess coronary blood flow which is a surrogate for cardiovascular outcomes. It is important to learn which factors are associated with cTFC. The goal of this study was to determine predictive models for epicardial blood flow assessed by cTFC and develop a diagnostic predictive model that indicates the individualized assessment of epicardial blood flow prior to primary percutaneous coronary intervention. This is a retrospective study including 3205 patients with ST-segment elevation myocardial infarction who underwent pPCI. The primary outcome was cTFC. Multivariable linear regression analysis was performed. Subsequently, a nomogram was developed to predict cTFC according to the candidate predictors. Median age was 58; the number of male patients was 2381 (74.3%). Median value of cTFC was 22 and interquartile range (IQR): 16.5–28.0). Age, diabetes mellitus (DM), total ischemic time, systolic blood pressure (SBP), heart rate (HR), and history of statin use remained in both full and reduced models. Our model may potentially allow clinicians to identify patients at high risk for impaired epicardial perfusion.